Analysis of Bureaucratic Communication in Building Organizational Culture at the Nusantara Capital Authority - Abdul Rahman; Martha Tri Lestari (Green Publisher Indonesia, 2026)
Bureaucratic communication is a strategic element in shaping the work culture and determining the performance of public organizations, especially in new government institutions that are in the institutional transition phase such as the Nusantara Capital Authority (OIKN). Hierarchical bureaucratic structures, differences in employee backgrounds, and cross-sector coordination demands have the potential to cause communication distortions that have an impact on the effectiveness of organizational work. This study aims to analyze how bureaucratic communication plays a role in the formation of organizational culture and its implications for organizational performance within the OIKN. The research uses a qualitative approach with a case study method. Data was collected through in-depth interviews, observations, document analysis, and targeted group discussions with leaders, structural officials, functional officials, special staff, and executive employees. The results of the study show that bureaucratic communication, which is still dominant, is top-down and formal, affecting the perception gap between job levels and hindering the internalization of organizational values. However, the implementation of two-way communication, the use of information technology, and participatory leadership communication styles have proven to be able to strengthen collaborative and adaptive organizational cultures, while increasing the effectiveness of coordination and organizational performance. This study concludes that strengthening open and integrated bureaucratic communication is the main prerequisite in building a healthy organizational culture and sustainable bureaucratic performance at OIKN.